‘What’s Up Doc?’ An Exploratory Study Investigating the Emotional Labour and its Potential Impact on the Emotional Wellbeing on General Practitioners in a Primary Care Setting - Farooqi, Maheen (2020)
General Practitioners examine, diagnose and advise unwell patients, they also provide emotional labour during their patient interactions. The purpose of this study was to explore the emotional labour that General Practitioners experience during their patient interactions and to understand the impact that it has on their emotional wellbeing. The study utilised the Conservation of Resources theory (Höbfoll, 1989), and the Job-Demand Resource theory (Demerouti and Bakker, 2011) to examine the links between emotional labour and job demands with emotional wellbeing.